Labeling of transgenic foods in Colombia and the power of information (2022)
The importance of labeling transgenic foods lies in the fact that labels constitute the communication mechanism between the producer and the consumer of a food; information that gives people the possibility to make rational decisions regarding food consumption, however, the omission regarding the mandatory labeling of transgenics present in Law 1480 of 2011, makes it difficult for people to exercise the right to make rational decisions regarding the consumption of transgenic foods. Consequently, the main objective of this article is to analyze the criteria of precaution and substantial equivalence applicable to the labeling of foods from genetically modified organisms -APOGM-, in order to make visible the importance of clear legal parameters in terms of labelled; understanding the labeling of transgenic foods as a presupposition to guarantee in Colombia the right to decide how to feed oneself, outlining the need for mandatory APOGM labeling to respond to the consumer's right to decide as a presupposition for human dignity and a protective mechanism for food sovereignty. With the aforementioned purpose, for the development of this article, the qualitative method was used, starting from the study of the APOGM labeling in the country and its incidence in terms of food sovereignty and guarantee of consumer rights, for this purpose the review of regulations, jurisprudence and scientific and academic literature on transgenic foods and their labeling; It is intended to glimpse the importance of strict food labeling, an issue that, referring to foods from genetically modified organisms, acquires relevance, since the label constitutes the means of control available to people to guarantee food sovereignty.